(untitled) (London Journal of Engineering Research, 2025)
For construction conditions, when it is necessary to determine the expected amount of subsidence of small-width structures on high-capacity loess bases having a soaking area larger than the area of the base of their foundation due to prolonged moistening by filtration flow, the compression compression model for determining relative subsidence becomes unacceptable.In addition, when determining the relative subsidence based on the results of compression tests, it is assumed that the soil of the loess base is deformed only in the vertical direction during moistening, while lateral deformations of the soil from the action of horizontal compacting stresses are not taken into account. However, as the results of comparing the calculations of many researchers of the expected subsidence with field data show, compression tests underestimate the additional deformations of structures that occur when their loess bases are moistened.